Young Offender Resistance Towards State hegemonic Practices: Case Study of “LPKA Belantara” - William Edward Maxey; Sri Setiawati; Zainal Arifin (Universitas Andalas, 2022)
The purpose of this article is to describe the resistance of young offenders toward hegemonic practices of the State. Following qualitative research practices with a descriptive design, this article employs the concept of habitus to analyze the nexus of actor and agency within the field of Belantara Young Offender Institution and the processes formed from resistance within the space. The findings show that young offenders attempt to resist the State’s control as they thwart the goals and values of the dominant power. The resistance of young offenders within Belantara Young Offender Institution consists of control of space, shaping discourse, rule-breaking, open defiance, conformity, and foot-dragging. Due to the imbalance of power between young offenders as a subaltern group and the staff at Belantara Young Offender Institution as the dominant group, the young offenders resist primarily through the hidden transcript. The data show a cycle of hegemony and resistance maintained by both groups which form a set of resistance. The research suggests the State reassess whether young offender institutions are the best place for young offenders as the cycle of hegemony and resistance creates a setting that cannot adequately rehabilitate.